New approaches in the empirical study of dreams - Bulkeley, Kelly (Poligrafi, 2023)
Dream research is entering a new era of accelerating insights and discoveries, thanks to the rise of powerful digital analysis tools that are enabling important advances in the empirical study of dreams. This paper illustrates the use of these tools, drawing on the resources of the Sleep and Dream Database, a free online archive of information about sleep and dreaming. These tools include statistical analyses of survey responses, systematic word searches of large collections of dream reports, and a well-grounded set of baseline frequencies to help with comparative measurement. The goal of this paper is to provide readers with an initial orienta-tion to the new world of dream discovery that has opened up because of tools like these. Several basic empirical findings are presented regarding clearly observable patterns of perception, emotion, and social interaction in dreaming. The paper will close with reflections on the emerging interplay of dreaming and technology.
Keywords: analiza vsebine; content analysis; continuity hypothesis; dreams; iskanje besed; sanje; teorija kontinuitete; word searching